Force majeure need for humanity to turn to nootechnology and nooecology - Korsak , K. V.; Korsak , Y. K. (Man and Environment. Issues of Neoecology, 2022)
We see the relevance of this article in the study of existing scientific papers on the prevention of global dangers. The population of Homo Sapiens Sapienses is growing quantitatively, increasing the rate of destruction of the natural environment and accelerating the movement to total collapse. Scientists around the world create only "appeals" and warnings of danger, even the UN decisions and the three environmental forums in 1992, 2002 and 2012 do not indicate real means of salvation.Purpose. A critical analysis of existing forecasts for the future and environmental projects and plans. The objectives of the study are to propose a real way to save humanity through the replacement of modern industrial and smart technologies with environmentally friendly production and social nooprocesses, development and use of noosciences, in particular, nooecology. The research methodology is based on the achievements of many classical and very young sciences, on the basis of which we build our proposal to create and use a large group of noosciences that form the author's nooglossary. The main ones are noointegral, systemic and noohistorical methods within the perspective principle of global evolutionism with transdisciplinary approaches.Results. Evidence that in the flow of nanotechnology since 2000 environmentally friendly, which we propose to call "wise"  ̶  nootechnology began to appear. They are few and the number is growing very slowly. Such technologies are considered impossible and are not included in national or world plans and projects. We present a fragment of our "Nooglossary", which contains "terms from the future". Unfortunately, it did not attract the attention of humanity, like the emotional & populist eco-declarations of Greta Thunberg, a girl from Sweden.Conclusion. In the context of the COVID-19 pandemic, we hope to use the little-known project "Plan S" to inform humanity about the existence of saving nootechnologies and noosciences. There was a force majeure need to immediately create not only nooecology, but also all the necessary noosciences. We claim that the nooera has already begun, but humanity has not yet noticed it. The UN Plan "17 Goals for Sustainable Development" should be transformed into a global document for the implementation of the noosymbiosis of humanity and the biosphere, and finally, to build the noosphere.